Colonisation and persistence of Escherichia coli 0157:H7 in the bovine gastro-intestinal tract - Naylor, Stuart Warren (The University of Edinburgh, 2003)
. coli 0157:H7 is a cause of infectious intestinal disease in humans, primarily in developed countries. Although not as prevalent as certain other bacterial enteropathogens, it is of particular concern due to the effect of a secreted virulence factor, shiga toxin (Stx), which causes potentially fatal systemic sequelae. Domestic ruminants, most frequently cattle, are consistently identified as the source of infection and transmission may occur through a variety of routes. The bacterium asymptomatically colonises the gastro- intestinal tracts (GIT) of its ruminant hosts. Adaptation to this niche is responsible for the presence of the organism within the environment. The principal aim during this study was to develop appropriate in vitro and in vivo systems to examine colonisation mechanisms of E. coli 0157:H7 in the bovine GIT. An adherence assay on cultured tissue explants was developed to compare different factors involved in E. coli 0157:H7 adherence. In two separate experiments the contribution of factors involved in intimate attachment, thought to be essential for virulence in humans, was assessed. The ability to intimately attach did not affect the level of E. coli 0157:H7 adherence to bovine intestinal epithelium in vitro. A strain lacking the genes required for intimate attachment however exhibited enhanced adherence to bovine Peyer's patch. The other strains did not exhibit a tropism for any of the tissue types examined.

The most relevant system to assess the behaviour of E. coli 0157:H7 is within its natural host. Persistent colonisation of weaned calves was achieved for a number of isolates marked by nalidixic acid resistance, including a Stx negative strain that colonised at a similar level and duration to the Stx positive co- strain. At the conclusion of each calf colonisation experiment, those individuals still shedding the organism were examined under necropsy to determine its distribution. The first attempts failed to recover the organism in significant numbers at any site examined despite it being present in ante -mortem faeces. One explanation was that the organism was multiplying primarily in the distal rectum. Further necropsies revealed that the organism was colonising the mucosal surface of the distal 3 cm of the rectum via intimate attachment and confirmed that this phenomenon was indeed typical of persistently colonised calves. This small region contained a high density of lymphoid tissue. Other bacteria are known to have a tropism for follicle- associated iv epithelium and it is proposed that E. coli 0157:H7 possesses an FAE specific factor that mediates its unique distribution within the bovine GIT and is responsible for many aspects of its biology resulting in its importance as a human pathogen